Plantar forefoot pressures in psoriatic arthritis-related dactylitis: an exploratory study. Issue 9 (September 2016) - Wilkins, Richard; Siddle, Heidi; Redmond, Anthony; Helliwell, Philip
Abstract Dactylitis is a common feature of psoriatic arthritis (PsA); local physical trauma has been identified as a possible contributing factor. The aim of this study was to explore differences in forefoot plantar pressures in patients with PsA with and without dactylitis and compare to healthy controls. Thirty-six participants were recruited into three groups: group A PsA plus a history of dactylitis; group B PsA, no dactylitis; group C control participants. Forefoot plantar pressures were measured barefoot and in-shoe at the left second and fourth toes and corresponding metatarsophalangeal joints. Temporal and spatial parameters were measured and data from the foot impact scale for rheumatoid arthritis (FIS-RA), EQ5D and health assessment questionnaire (HAQ) were collected. Pressure time integral peak plantar pressure, and contact time barefoot and in-shoe were not significantly different between groups. Temporal and spatial parameters reported no significant differences between groups. ANOVA analysis and subsequent post hoc testing using Games-Howell test yielded significance in FIS-RA scores between both PsA groups versus controls, Ap ≤ 0.0001 and PsA group Bp < 0.0001 in the FIS-RA impairment and footwear domain, PsA group Ap < 0.03 and PsA group Bp ≤ 0.05 in the FIS-RA activity and participation domain compared to controls. This is the first exploratory study to investigate forefoot plantar pressures in patients with and without historical dactylitis in PsA. FIS-RA scores indicate PsA patients have significant limitations compared to controls, although a history of dactylitis does not appear to worsen patient reported outcomes.